Preparation and self-assembly properties of surface active hydrophobically associating polyacrylamide. Issue 1 (2nd January 2019) - Su, GaoShen; Luo, Yue; Li, Fan; Yu, Xiaorong
ABSTRACT: A novel surface-active polymer (PCPAM) was synthesized by free-radical polymerization of acrylamide (AM), 2-acrylamido-2-methyl propane sulfonic acid (AMPS) and surfmer (ACP) which was previously prepared by reacting Nonaphenol polyethyleneoxy ether-10 (OP-10) and allyl chloride. The structure of PCPAM was characterized by FT-IR, 1 H-NMR, GPC and TGA. In addition, the self-assembly properties of the copolymer were studied with viscosimetry and fluorescence probe method. Moreover, the activity of PCPAM solution was examined with surface tension, IFT and emulsifying ability. Results indicated that, the solution viscosity proportionally increased with PCPAM concentrations, leading in the formation of a three-dimensional network with surface activity and thermal stability, and the CAC of PCPAM was about 1.5 g/L, PCPAM can reduce the interfacial tension between crude oil and water, the IFT value was about 0.029 mN/m when the concentration of PCPAM beyond CAC and have good ability to form stable emulsions. Furthermore, the core flooding experimental demonstrated that the oil displacement efficiency of PCPAM increased by about 17.4%, which is better than 13.87% and 15.55% based on HPAM flooding and HPAM/surfactant flooding, respectively. All of these properties indicate that the PCPAM was an excellent chemical for chemical enhanced oil recovery.